Evaluation of a Serious and Violent Offender Reentry Initiative (SVORI) Program in a Midwest State - Veeh, Christopher A. (Criminal justice policy review, 2017)
The Serious and Violent Offender Reentry Initiative (SVORI) paved the way for a new era of rehabilitation in corrections’ programming. However, published outcome evaluations of SVORI programs and their progeny are limited in number. The current article presents the multiyear outcome evaluation of one prisoner reentry initiative established in a Midwestern state, which was developed within the framework of the SVORI program model. A comparison group was identified using propensity score matching to evaluate program effectiveness on the recidivism outcomes of returns to prison and new convictions. Cox proportional hazards modeling found program participants to have significantly lower hazard to incur a new conviction than the comparison group but no difference in the hazard for reincarceration. The implications of these mixed findings in recidivism outcomes are discussed for the reentry program initiative.